2023
DOI: 10.1002/cssc.202202017
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effect on Photoelectrochemical Water Splitting Toward Highly Solar to Hydrogen Efficiency

Abstract: Photoelectrochemical (PEC) hydrogen production is an emerging technology that uses renewable solar light aimed to establish a sustainable carbon‐neutral society. The barriers to commercialization are low efficiency and high cost. To date, researchers have focused on materials and systems. However, recent studies have been conducted to utilize thermal effects in PEC hydrogen production. This Review provides a fresh perspective to utilize the thermal effects for PEC performance enhancement while delineating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 168 publications
0
13
0
Order By: Relevance
“…Arrhenius equation can further describe the relationship between the rate constant of a chemical reaction and temperature. 100,101…”
Section: Thermal Barrier In Water Splitting Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrhenius equation can further describe the relationship between the rate constant of a chemical reaction and temperature. 100,101…”
Section: Thermal Barrier In Water Splitting Reactionmentioning
confidence: 99%
“…As mentioned above, overall water splitting is an endothermic reaction. Arrhenius equation can further describe the relationship between the rate constant of a chemical reaction and temperature 100,101 k=AeEaRT0.25emnormalonormalr0.25emnormallnormalnk=EaRT+normallnormalnA where k , A , E a , R , and T are rate constant, pre‐exponential factor, the activation energy for the reaction, universal gas constant, and absolute temperature, respectively.…”
Section: Unconventional Strategiesmentioning
confidence: 99%
“…Therefore, the rational utilization of both IR light and heat carried and converted from light has emerged as a compelling research topic in the field of solar PEC applications. To date, several studies have reported photothermal effect induced through the incorporation of IR-responsive materials onto the PEC electrode, which primarily contributes to lowering the energy barrier for reaction and improving carrier mobility. Hence, the development of a novel PEC electrode with full-spectrum light absorption to enhance water splitting through the establishment of a photothermo-electro coupling field represents an effective strategy for addressing the aforementioned limitations.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, based on the comprehensive analysis of existing literature on single and binary photoanodes composed of these three materials for water splitting, it becomes evident that the thermal effect resulting from light has often been overlooked. Nevertheless, recent studies have emerged to harness this thermal effect in PEC reaction, showcasing a significant augmentation in PEC performance. If primarily generated through solar photothermal conversion rather than external heating, this thermal effect holds great potential to elevate solar utilization efficiency to a new level. With this in mind, the surface modification of NP on the CZS/TNA photoanode offers an additional advantage: an increase in the photoanode surface and electrolyte temperatures owing to its reliable photothermal conversion ability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this significant progress, CN photoanodes still exhibit low photocurrent density and total efficiency compared to the best photoanodic materials. [19,20] The PEC performance of CNbased materials is currently hindered by three main limitations: 1) moderate light-harvesting properties; 2) the poor charge separation and transfer efficiency of unmodified CN; and 3) slow oxygen evolution reaction (OER, i.e., water oxidation) kinetics. [21][22][23] Recently, several studies have shown how the optical and electronic properties of CN materials may be modified by using alkaline metal cations (K and Na) [24][25][26] and heteroatoms (such as B, [27] S, [28] O, [29] and P [30] ) as dopants.…”
Section: Introductionmentioning
confidence: 99%